Study on the electromagnetic property and microwave heating efficiency of concrete with magnetite aggregate. (1st August 2022) - Wang, Zhihang; Bai, Erlei; Huang, He; Wang, Tengjiao; Sun, Huiying
Highlights: The electromagnetic property of concrete with magnetite aggregate was studied. The microwave heating efficiency of concrete with magnetite aggregate was studied. The mechanism for action of magnetite aggregate on microwave heating efficiency of concrete was analyzed. Abstract: As an excellent absorbing material, natural magnetite with high microwave heating capacity may be used for deicing cement concrete road. In order to remove ice and snow on road surface quickly and effectively, in exploration of the microwave deicing technology, 6 kinds of concrete with different magnetite aggregate content were prepared with magnetite gravel as the absorbing material, and the influence of magnetite aggregate on mechanical properties, electromagnetic properties, microwave heating efficiency and microwave deicing efficiency of concrete was investigated. The results showed that magnetite aggregate improved both compressive strength and flexural strength of concrete significantly, and also enhanced its electromagnetic properties, microwave heating efficiency and microwave deicing efficiency greatly. For the concrete with magnetite aggregate, when the height of waveguide port was 55 mm, the microwave heating efficiency was optimal. With the increase of magnetite aggregate content, the microwave heating efficiency of concrete increased gradually. After the addition of magnetite aggregate, the dielectric loss capacity of concrete was improved obviously, and the magnetic polarization loss capacity was improved to a certain degree. The improvement in microwave heating efficiency of concrete with magnetite aggregate was closely related to the increase of imaginary part of the complex dielectric constant. Magnetite gravel can be used as aggregate and absorbing material of cement concrete for efficient microwave deicing.